2016
DOI: 10.1136/bmjopen-2016-012548
|View full text |Cite
|
Sign up to set email alerts
|

Is Walk Score associated with hospital admissions from chronic diseases? Evidence from a cross-sectional study in a high socioeconomic status Australian city-state

Abstract: ObjectivesTo explore patterns of non-communicable diseases (NCDs) in the Australian Capital Territory (ACT).To ascertain the effect of the neighbourhood built environmental features and especially walkability on health outcomes, specifically for hospital admissions from NCDs.DesignA cross-sectional analysis of public hospital episode data (2007–2013).SettingHospitalisations from the ACT, Australia at very small geographic areas.ParticipantsSecondary data on 75 290 unique hospital episodes representing 39 851 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…The WS measures neighborhood characteristics on a scale of 0 (poorest walkability) to 100 (greatest walkability) based on distance and a variety of key public and commercial destinations (e.g., grocery stores, retail stores, parks, schools). The WS has been validated to be correlated with objective neighborhood walkability indexes based on geographic information systems data [20], and has been demonstrated to be related to physical activity levels and associated with health outcomes in the general population [19, 21, 22]. It has been shown in the general population that the probability of people meeting physical activity recommendations increases by 26% for every 10-point increase in the WS [19].…”
Section: Introductionmentioning
confidence: 99%
“…The WS measures neighborhood characteristics on a scale of 0 (poorest walkability) to 100 (greatest walkability) based on distance and a variety of key public and commercial destinations (e.g., grocery stores, retail stores, parks, schools). The WS has been validated to be correlated with objective neighborhood walkability indexes based on geographic information systems data [20], and has been demonstrated to be related to physical activity levels and associated with health outcomes in the general population [19, 21, 22]. It has been shown in the general population that the probability of people meeting physical activity recommendations increases by 26% for every 10-point increase in the WS [19].…”
Section: Introductionmentioning
confidence: 99%
“…Although some reports investigated the correlation between built environment attributes and cardiovascular disease and stroke incidence [32,33], few reports from around the world have investigated the correlation between perceived built environment attributes and physical activity after such diseases [16,17,34].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, several indices such as the Walk Score, Walkability Index, and Pedestrian Index of the Environment were developed combining various built environmental variables that influence walking behavior [7,[19][20][21][22][23][24][25][26][27][28][29][30][31][32]. The Walk Score is one of the popular indices that objectively measures neighborhood walkability, taking into account the accessibility of amenities in the vicinity (e.g., grocery stores, restaurants, shopping centers, coffee shops, parks, schools) and pedestrian friendliness (e.g., intersection density and average block length) [25], and is currently used in various fields, including public health, real estate, and urban planning [33][34][35][36][37]. Studies have verified whether the Walk Score is appropriate to describe the level of walkability, and correspondingly, several works of the literature showed that a higher level of Walk Score is positively correlated with walking behavior [7,26,29,30,[38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%